Optimal design and modelling of complaint micro-linkage mechanism - Khan, Md. Raisuddin (IIUM Press, 2009)
In this project we investigate the feasibility of using the pseudo-rigid-body modelling technique in examining a simple modular compliant mechanism. An optimum design is tested through a modelling technique built around the concept of the pseudo-right-body. A mathematical model is constructed to determine the non-linear behavior of large-deflections. The problem is solved using an iterative method as it cannot be simplified to a closed loop equation. The solution to the non-linear model is then compared to empirical results collected from a mock up of the compliant device. The pseudo-rigid-body model is then combined with a linear model to develop the complete solution, which is determined to be fairly close to the actual behavior of the mock up. The dynamic analysis is then conducted on the same model, where the solution from the model is used alongside numerical methods in the MATLAB environment. Finally, possible applications of this device are briefly discussed.